1982
DOI: 10.1128/aem.43.2.284-288.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid concentration on growth on meat of Gram-negative psychrotrophs from a meatworks

Abstract: The inhibitory effect of the lactic acid in meat on gram-negative psychrotrophs appears to be due mainly to the decrease in pH, not to action of the undissociated acid. Species of Pseudomonas were essentially unaffected by the pH of normal meat. Other gram-negative psychrotrophs isolated from a meatworks included a large number of strains which would not grow on meat of normal pH at chill temperatures. Raising either the pH or the incubation temperature allowed many of the pH-sensitive strains to initiate grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…For pork, greater differences were observed at the beginning of the storage, but the counts of Pseudomonas spp. rapidly converged to the TVC when the exponential growth phase started as has already been reported (Gill & Newton, 1982;Blickstad & Molin, 1983;Coates et al, 1995;Lebert et al, 2000Lebert et al, , 2005Olsson et al, 2003). Furthermore, significant (P < 0.05) high correlations were observed between the count of Pseudomonas spp.…”
Section: Resultssupporting
confidence: 77%
“…For pork, greater differences were observed at the beginning of the storage, but the counts of Pseudomonas spp. rapidly converged to the TVC when the exponential growth phase started as has already been reported (Gill & Newton, 1982;Blickstad & Molin, 1983;Coates et al, 1995;Lebert et al, 2000Lebert et al, , 2005Olsson et al, 2003). Furthermore, significant (P < 0.05) high correlations were observed between the count of Pseudomonas spp.…”
Section: Resultssupporting
confidence: 77%
“…In agreement with the results of Gill and Newton (1982) and our previous study (Van Netten et al 1997), we found that the inhibitory effect on bacteria in meat appears to be due mainly to a decrease in pH. The pH value permitting growth of Salm.…”
Section: Discussionsupporting
confidence: 93%
“…Carrageenan-based, low-fat ground beef pattie treatments containing 2 or 3% potassium lactate (LCLZ & LCL3) had lower aerobic plate counts and psychrotrophic populations than either the all-beef patties (AB) or carrageenan-based patties with no lactate (LC). Gill and Newton (1982) indicated that the inhibitory effect of lactic acid on microbial growth in meat was the result of decreased pH. However, addition of the undissociated acids such as potassium or sodium lactate has little effect on pH as explained earlier.…”
Section: Microbial Growthmentioning
confidence: 78%
“…Lactic acid is well known for its ability to inhibit microbial growth. The inhibition of proteolytic microbial growth by lactic acid has been shown to be primarily the result of a decrease in pH (Gill and Newton, 1982). In recent years sodium and potassium lactates have been established as food ingredients for their enhancement of flavor and preservative properties.…”
Section: Introductionmentioning
confidence: 99%